Negative terpinen-4-ol modulate potentially malignant and malignant lingual lesions induced by 4-nitroquinoline-1-oxide in rat model - Neto, José Nunes Carneiro; Sorbo, Juliana Maria [UNESP]; Filho, Carlos Alberto Arcaro [UNESP]; Sabino, Thaís Fernanda Moreira [UNESP]; Ribeiro, Daniel Araki; Brunetti, Iguatemy Lourenço [UNESP]; de Andrade, Cleverton Roberto [UNESP] (Springer Nature, 2022)
Our aim was to verify the modulative TP-4-ol capacity in 4-nitroquinoline-1-oxide induced oral rat cancer. The stereoisomers of TP-4-ol were used against the human tongue squamous cell line and the negative stereoisomer showed lower IC50. Thirty-one Holtzman rats (120–130 g) were cancer-induced by 4-nitroquinoline-1-oxide (4-NQO/8 weeks/25 ppm) and 32 Holtzman rats (120–130 g) were used to healthy and TP-4-ol toxicity experiments. Six groups were used, healthy, 0.1nL/g of TP-4-ol, 8nL/g of TP-4-ol, 4-NQO, 4-NQO + 0.1nL/g of TP-4-ol, and 4-NQO + 8nL/g of TP-4-ol. We performed the toxicity analysis by biochemical and histopathological analysis. The biochemistry analysis includes alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate transaminase (AST), urea, and creatinine and the histopathology analysis includes the liver, kidney, lung, and spleen. Specifically, for malign modulation, we performed a macroscopic and microscopic analysis. The group exposed to 0.1nL/g of TP-4-ol demonstrated a reduced risk of malignancy in dysplasia considering the criteria of architecture and cytology. Similarly, a drop of percentual rats with SCC diagnosis was observed in 4-NQO + 0.1nL/g (41.6%) when compared to 4-NQO (87.5%). Moreover, the 4-NQO group presented a median of 2.62 SCC/rat and the 4-NQO + 0.1nL/g demonstrated a median of 0.75 SCC/rat. For toxicity analysis, 4-NQO + 0.1nL/g showed focal necrosis in the kidney and 4-NQO showed lung hemorrhagic areas. The concentration of 0.1nL/g was more effective in reducing the tongue induction of potentially malignant and malignant lesions by 4-NQO. A kidney toxicity was observed in healthy animals exposed to 0.1nL/g of TP-4-ol. The negative isoform of terpinen-4-ol negatively modulates the development of potentially malignant and malignant lesions in rats (Rattus nonverdicts albinos, Holtzman) exposed to 4-NQO. (-)-Terpinen-4-ol reduced the mice percentual with squamous cell carcinoma, 87.5 to 41.6%, and decreased the cancer/rat ratio of 2.62 in 4-NQO to 0.75 in 4-NQO + 0.1nL/g. This represents 52.4% by group and 71.3% in the cancer/rat ratio.
Keywords: 4-Nitroquinoline-1-oxide; Oral cancer modulation; Terpinen-4-ol; Toxicity